2016
DOI: 10.1634/theoncologist.2015-0502
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Prolactin Receptor Antagonist LFA102 in Metastatic Breast and Castration-Resistant Prostate Cancer

Abstract: Lessons LearnedDespite evidence for a role for prolactin signaling in breast and prostate tumorigenesis, a prolactin receptor-binding monoclonal antibody has not produced clinical efficacy.Increased serum prolactin levels may be a biomarker for prolactin receptor inhibition.Results from the pharmacokinetic and pharmacodynamics (PD) studies suggest that inappropriately long dosing intervals and insufficient exposure to LFA102 may have resulted in lack of antitumor efficacy.Based on preclinical data, combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
2
47
0
2
Order By: Relevance
“…We therefore generated REGN2878-DM1, comprised of a fully human anti-PRLR antibody, REGN2878, and the cytotoxic drug DM1. We found high expression of PRLR in approximately 25% of breast cancers across previously established molecular subtypes defined by HER2, ER, and PR expression, in agreement with other published reports (12,24). Of note, we found that that PRLR may be expressed in some triple-negative breast cancers (TNBC), as these tumors remain in need of novel targeted therapeutics.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We therefore generated REGN2878-DM1, comprised of a fully human anti-PRLR antibody, REGN2878, and the cytotoxic drug DM1. We found high expression of PRLR in approximately 25% of breast cancers across previously established molecular subtypes defined by HER2, ER, and PR expression, in agreement with other published reports (12,24). Of note, we found that that PRLR may be expressed in some triple-negative breast cancers (TNBC), as these tumors remain in need of novel targeted therapeutics.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, this antibody was conjugated to the auristatin MMAE to form the ADC Adcetris (brentuxmab vedotin) that has demonstrated significant antitumor activity in Hodgkin's Lymphoma and Anaplastic Large Cell Lymphoma clinically (52). Perhaps similarly, the anti-PRLR antibody LFA102 was recently observed not to have sufficient activity in clinical testing against PRLR-positive cancers despite its inhibition of PRLR signaling (24). Doses of LFA102 up to 60 mg/ kg did not show dose-limiting toxicities, suggesting that blocking PRLR is well tolerated, although the tolerability of anti-PRLR ADCs will have to be assessed in appropriate toxicology studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because dopamine is unable to down-regulate PRL production in extrapituitary tissues, alternative therapeutic approaches have been developed to block PRLR-mediated signaling rather than PRL production in target cells [54,55]. A phase I clinical trial with PRLR neutralizing antibodies in patients with breast or prostate cancer, however, showed no antitumor activity when used as monotherapy [56]. Still, the results presented here support the rationale to test this approach in chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 64%
“…Since truncated PRLR expression is preferentially increased in ERα+ breast cancer and FL/T PRLR heterodimers display constitutive activation as shown in our current study, it would be of interest to examine whether LFA102 is able to block heterodimerization of full-length and truncated PRLR in future studies. Unfortunately, LFA102 failed to show antitumor efficacy in a recent Phase 1 clinical trial for metastatic breast cancer (Agarwal et al, 2016). Direct inhibition of Jak2 using small molecule inhibitors will also be worthy of investigation in breast cancers with Prlr activation.…”
Section: Discussionmentioning
confidence: 99%